RISK FACTORS ASSOCIATED WITH CHRONIC ENERGY DEFICIENCY (CED) IN PREGNANT WOMEN - Hutapea, Lowisa Kristina; Noor , Meitria Syahadatina; Hartoyo , Edi; Triawanti, Triawanti; Sadiqi , Muhammad Abdan (Indonesian Midwifery and Health Sciences Journal, 2025)
Background: Chronic Energy Deficiency is a nutritional problem in pregnancy. The percentage of pregnant women with Chronic Energy Deficiency is the 5th highest among Puskesmas Basarang due to the consequences caused by Chronic Energy Deficiency in Puskesmas Basarang from 2023 to August high in Puskesmas Basarang as much as 22.90%. The study purposed to find out the relationship between maternal knowledge about nutrition, husband's support, family income, maternal age, and pregnancy distance with the incidence of CED in pregnant women in the working area of Puskesmas Basarang, Kapuas Regency in 2023. Method: The research was analytical observational with a cross sectional approach, the sample was 66 pregnant women in the Basarang Community Health Center Working Area, Kapuas Regency, taken using the total sampling technique. The research instrument used a questionnaire. Result: The results of the multivariate test of the variabel of maternal knowledge about nutrition were most associated with the incidence of CED in pregnant women (Exp(B) = 11.655). Conclusion: The most dominant variabel with the incidence of SEEK in pregnant women is maternal knowledge about nutrition.